2019
DOI: 10.1007/s00221-019-05495-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrocorticographic changes in field potentials following natural somatosensory percepts in humans

Abstract: D=digit (e.g. D1 is digit 1) Supplementary fig. 1 Location and type of somatosensory percepts throughout the implanted grids. Grids mapped onto 3-D reconstructions of the brain based on a merge of pre-operative magnetic resonance imaging and post-operative computed tomography scans on the left, and later grids with somatosensory percepts on the right. The purple line estimates the central sulcus and the green bar is added to match the orientation. The bipolar combination produced self-reported sensations, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Human fMRI studies suggest disruption in the central executive network (active at external task demands) and the default mode network (active at wakeful rest) in patients with delirium. Both networks involve the prefrontal cortex 74,114 and are consistent with the network dysconnectivity hypothesis of delirium. 87,89 These regionspecific hypotheses for delirium could be tested in animal models with direct neurophysiological recording; however, unlike EEG, the low temporal resolution of most types of brain imaging require that the animal be motionless for long periods, implying the use of anesthetics, which could confound the results.…”
Section: Functional Magnetic Resonance Imagingsupporting
confidence: 75%
See 1 more Smart Citation
“…Human fMRI studies suggest disruption in the central executive network (active at external task demands) and the default mode network (active at wakeful rest) in patients with delirium. Both networks involve the prefrontal cortex 74,114 and are consistent with the network dysconnectivity hypothesis of delirium. 87,89 These regionspecific hypotheses for delirium could be tested in animal models with direct neurophysiological recording; however, unlike EEG, the low temporal resolution of most types of brain imaging require that the animal be motionless for long periods, implying the use of anesthetics, which could confound the results.…”
Section: Functional Magnetic Resonance Imagingsupporting
confidence: 75%
“…Direct, more invasive neurophysiological activities, such as local field potentials, single neuron activity, and brain microdialysis (directly measuring neurotransmitter levels), could provide critical insights into the neurophysiological mechanisms of delirium. While becoming possible in human cohorts (eg, electrocorticography recordings prior to epilepsy resection and brain‐computer interface studies 114‐118 ), direct neural recordings are primarily applicable only to preclinical animal models. In particular, the brain regions that represent specific cognitive functions or neurotransmitter systems can be directly tested in animal models 87,89 .…”
Section: Introductionmentioning
confidence: 99%
“…Others reported that low gamma ERS (40-60 Hz) often started at or after grasp onset and could last longer than the movements, suggesting that it may be linked to a combination of movement execution and sensory feedback related modulations (Crone et al, 1998;Szurhaj et al, 2005). Together with phasic response of fast adapting receptors, it is likely that the fast firings generated by the slowly adapting Ruffini endings and Merkel cells contribute to the early high-intensity broadband gamma response that we observed ( Figure 5) by way of skin deformation, indentation, as well as pressure at the onset of the grasp (Roudaut et al, 2012;Ryun et al, 2017b;Delhaye et al, 2018;Kramer et al, 2019). The broadband high-frequency ERS later reduces to a low-intensity gamma response at a lower frequency as time progresses and this behavior can be related to the activation patterns of the slowly adapting receptors of the afferent system (Roudaut et al, 2012;Delhaye et al, 2018).…”
Section: Connections To the Dynamics Of The Afferent Systemmentioning
confidence: 84%
“…Others also briefly mentioned the presence of biphasic peaks of ERS in human ECoG during hand grasp (Flint et al, 2017). Interestingly, recent work on the response to deep, light and soft touch (Kramer et al, 2019) with ECoG showed that elevations in HG power seen within selected electrodes over the hand area of primary somatosensory cortex (S1), lasted between around 300 and 500 ms, but extinguished prior to the end of the tactile stimulus. This coincides with our findings regarding the S1 high-gamma attenuation pattern during the hold period of a grasp task and Figure 3 shows that high-intensity gamma response (50-150 Hz) peaked between 50 and 400 ms after grasp onset, within selected electrodes anterior and posterior to the central sulcus.…”
Section: Temporal Dynamics Of Lfb-erd and Hfb-ersmentioning
confidence: 99%
“…Investigators suggest that eye closure-related alpha augmentation is correlated to functional idling of cortical areas. 2,3,37 Task-related alpha attenuation has been reported to be temporarily coupled with high-gamma augmentation in many iEEG studies of motor, 15,75,76 somatosensory, 77,78 visual, 16,17,79,80 auditory, 81,82 memory, 83,84 and language function. [85][86][87][88] Investigators suggest that task-related high-gamma augmentation is more accurately time-locked to a given behavior and spatially more confined to the eloquent cortex.…”
Section: Significance Of Functional Connectivity Modulationsmentioning
confidence: 99%